The effect of home-based intervention program on blood profiles among undergraduate female students in Iraq - Soh, Kim Geok; Noori, Jian Abdullah; Soh, Kim Lam; Japar, Salimah; Yusof, Aminuddin (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
The aim of this study is to ascertain whether a home-based physical activity and dietary awareness intervention program could improve blood profiles of sedentary undergraduate female students in Iraq. A 12-weeks home-based randomised controlled trial was conducted on 44 undergraduate female students from Soran university, Iraqi. Both experimental (n=22) and control (n=22) groups completed practical tests at baseline, post-test1, and post-test2, but only the experimental group participants received the 12-weeks intervention program. The field tests were used to measure all blood profiles variables. Results showed that the experimental group demonstrated improvement in diastolic systolic blood pressure after undergone 6 weeks post-test intervention program. The reported f value was (F(2, 84)=-6.636, p=.047, η2=0.091). Significant blood profiles results were reported for diastolic blood pressure and blood glucose. However, the significant results were only reported after the subjects had undergone the 12-weeks intervention program. The reported f values were (F(2, 84)=-7.000, p=.007, η2=0.163) and (F(2, 84)=-16.182, p=.003, η2=0.188), respectively. As the conclusion, a home-based physical activity and dietary intervention program can positively influence sedentary undergraduate female students’ blood profiles and the benefits can be achieved as early as after 6-weeks.